Comparing relations of ethnic-racial public regard, centrality, and intergroup contact attitudes among ethno-racially diverse adolescents. (June 2022) - Wantchekon, Kristia A.; Umaña-Taylor, Adriana J.; McDermott, Elana R.; Sladek, Michael R.; Rivas-Drake, Deborah; Agi, Abunya C.; Satterthwaite-Freiman, Megan
The current cross-sectional study examined how adolescents' appraisal of how positively others viewed their ethnic-racial group (i.e., public regard) and how integral their ethnic-racial background was to their self-concept (i.e., centrality) related to their intergroup contact approach and avoidance attitudes. Participants were Black, Latinx, and White high school students ( N = 2, 609; M age = 16.39, SD = 1.16; 52% female) from the U.S. Southwest and Midwest. Utilizing multigroup structural equation modeling, results indicated that across all ethnic-racial backgrounds, and regardless of geographical context, public regard was positively associated with approach attitudes. Conversely, findings for avoidance attitudes varied by ethnic-racial background. Specifically, public regard was negatively associated with avoidance attitudes for White adolescents, whereas this relation was null for Black and Latinx adolescents. Additionally, although centrality was positively associated with avoidance attitudes among all adolescents, the relation was stronger among White adolescents than among Black and Latinx adolescents.